Ruthenium(II) complexes coordinated to graphitic carbon nitride: Oxygen self-sufficient photosensitizers which produce multiple ROS for photodynamic therapy in hypoxia. (September 2021) - Wei, Fangmian; Kuang, Shi; Rees, Thomas W.; Liao, Xinxing; Liu, Jiangping; Luo, Diqing; Wang, Jinquan; Zhang, Xiting; Ji, Liangnian; Chao, Hui
Abstract: The photodynamic therapy (PDT) of cancer is limited by tumor hypoxia as PDT efficiency depends on O2 concentration. A novel oxygen self-sufficient photosensitizer (Ru-g-C 3 N 4 ) was therefore designed and synthesized via a facile one-pot method in order to overcome tumor hypoxia-induced PDT resistance. The photosensitizer is based on [Ru(bpy)2 ] 2+ coordinated to g-C 3 N 4 nanosheets by Ru–N bonding. Compared to pure g-C 3 N 4, the resulting nanosheets exhibit increased water solubility, stronger visible light absorption, and enhanced biocompatibility. Once Ru-g-C 3 N 4 is taken up by hypoxic tumor cells and exposed to visible light, the nanosheets not only catalyze the decomposition of H2 O2 and H2 O to generate O2, but also catalyze H2 O2 and O2 concurrently to produce multiple ROS ( OH, O2 −, and 1 O2 ). In addition, Ru-g-C 3 N 4 affords luminescence imaging, while continuously generating O2 to alleviate hypoxia greatly improving PDT efficacy. To the best of our knowledge, this oxygen self-sufficient photosensitizer produced via grafting a metal complex onto g-C 3 N 4 is the first of its type to be reported. Graphical abstract: A novel oxygen self-sufficient photosensitizer (Ru-g-C 3 N 4 ) was constructed from cis -Ru2 (bpy)2 Cl2 and g-C 3 N 4 by Ru–N coordination to achieve enhanced PDT in hypoxia. Ru-g-C 3 N 4 not only catalyze the decomposition of H2 O2 and H2 O to generate O2, but also catalyze H2 O2 and O2 concurrently to produce multiple ROS ( OH, O2 −, and 1 O2 ) for the treatment of cancer both in vitro and in vivo . Moreover, Ru-g-C 3 N 4 can be used for in vivo luminescence imaging to allow highly precise treatment. Image 1